Computational Analysis of Mercury Contamination in Gold-Bearing Soils and its Impact on Health of People - Carlos Chavarry-Vallejos; Joaquín Támara-Rodríguez; Liliana Chavarría-Reyes; Carla Poma-González; Enriqueta Pereyra-Salardi; Carlos Bancayán-Oré; Jainer Solorzano-Poma; Ítalo Diaz-Horna; Fernando Javier Depaz Hidalgo; Elizabeth Clotilde Panana Holgado (Migration Letters, 2023)
In this study, an exhaustive mathematical analysis of mercury transport in contaminated soils was carried out to clarify the extent of its environmental impact and possible remediation strategies. To this end, a rigorous mathematical model has been used, and a convergence and stability analysis has been carried out, considering a range of relevant parameters associated with mercury. This analysis involves discretizing the relevant differential equations, which allows us to quantitatively assess the impact of mercury on both the soil matrix and human health. The key findings of this study reveal that mercury concentration tends to decrease with soil depth. However, the environmental effects and implications for human health are significant. This analytical approach provides a deeper understanding of mercury dynamics in contaminated soils and crucial information supporting informed decision-making regarding remediation strategies and environmental and health risk management.